Structural and developmental expression of Ss-riok-2, an RIO protein kinase encoding gene of Strongyloides stercoralis - Wei-Qiang Lei (Nature Portfolio, 2017)
Abstract RIO kinases are essential atypical protein kinases in diverse prokaryotic and eukaryotic organisms, playing significant roles in yeast and humans. However, little is known about their functions in parasitic nematodes. In the present study, we have isolated and characterized the full-length cDNA, gDNA and a putative promoter of a RIOK-2 protein kinase (Ss-RIOK-2) encoding gene (Ss-riok-2) from Strongyloides stercoralis, a medically important parasitic nematode (Order Rhabditida). A three-dimensional structure (3D) model of Ss-RIOK-2 was generated using the Chaetomium thermophilum RIOK-2 protein kinase (Ct-RIOK-2) crystal structure 4GYG as a template. A docking study revealed some critical sites for ATP binding and metal binding. The putative promoter of Ss-riok-2 contains a number of conserved elements. RNAseq analysis revealed the highest levels of the Ss-riok-2 transcript in free-living females and parasitic females. To identify anatomical patterns of Ss-riok-2 expression in S. stercoralis, we observed expression patterns of a transgene construct encoding green fluorescent protein under the Ss-riok-2 promoter in post free-living S. stercoralis. Expression driven by this promoter predominated in intestinal cells. This study demonstrates significant advancement in molecular and cellular biological study of S. stercoralis and of parasitic nematodes generally, and provides a foundation for further functional genomic studies.